Method for Conversational Voice Quality Evaluation in Cellular Networks - Kajackas, A.; Anskaitis, A.; Gursnys, D. (Elektronika ir Elektrotechnika, 2011)
In this paper, method for evaluation of varying conversational speech quality in wireless communications is proposed. The proposed algorithm evaluates quality degradations using indicators based on count of lost frames and voice activity indications. The correctness of proposed algorithm is investigated by comparison of test results with results obtained using PESQ algorithm under same conditions. The achieved average correlation coefficient is 0.975. This result is independent of frame loss model and percentage of silence in test sentences. Proposed algorithm can be implemented in mobile stations and used for speech quality evaluation by real conversation. Ill. 3, bibl. 13, tabl. 3 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.109.3.182